Effectual surgical perineal reconstruction of malignant mucosal vulvar melanoma - Ying-Xuan Li; Wen-Chun Chang; Kuan-Ju Huang; Chin-Jui Wu; Lin-Hung Wei; Bor-Ching Sheu (Elsevier, 2023)
Objective: To demonstrate a successful surgical treatment and reconstruction in a case of malignant mucosal vulvar melanoma. Case report: A 52-year-old woman had stage II bulky malignant mucosal vulvar melanoma and received wide surgical excision with partial vulvectomy. She underwent 2-steps reconstructive vulvoplasty and vaginoplasty with skin grafting 1 year after initial surgical treatment. There was no evidence of recurrence after 3 years of follow-up. Conclusion: Vulvar melanoma is a rare malignant neoplasm. Wide local excision with reconstruction can relieve pelvic discomfort and restore local function after the surgery.